Sustainability in port terminals with the application of Artificial Intelligence - Voong, Tony; Kivistö, Pontus (My University, 2024)
This study explores the potential of artificial intelligence (AI) to enhance social and economic sustainability within port terminal, by using technologies such as machine vision, machine learning, machine hearing and sensors. AI holds promise in improving safety for terminal workers through enhanced equipment monitoring and risk mitigation. Furthermore, the application of AI predictions can create a analytical measurement for facility efficient space utilization and accurate forecasting of goods movement, enable economic sustainability through cost reduction and revenue optimization. However, the realization of AI's potential in port terminals is hindered by economic constraints and data availability. Investments and data input/parameters are crucial for enabling effective AI implementation. Further research is needed to provide evidence supporting AI's role in advancing social and economic sustainability within port terminal operations.
Keywords: Artificiell intelligens; Hamnterminal; Terminal; Maskin inlärning; Ekonomisk hållbarhet; Social hållbarhet; Fyllnadsgrad; Artificial intelligence; Port terminal; Terminal; Machine learning; Economic sustainability; Social sustainability; Utilization